Case Study : Projek Outdoor / Aisyah Harun - Harun, Aisyah (2021)
Regarding to fulfill my individual assignment for Fundamental of Entrepreneurship (ENT300), I need to conduct a case study which is a case study based on company’s information. In this case study, company that I chose is Project Outdoor. Because of pandemic Covid-19, I had an interview session with the director of Projek Outdoor through Whatsapp application to get more information about his business. Mohammad Nazirul Nazrin bin Abdul Rahman is Director of Projek Outdoor. The interview session was going smoothly. I got a lot of information about a background of the company.